Pembangunan Perdamaian Pasca-Konflik di Indonesia: Kaitan perdamaian, pembangunan dan demokrasi dalam pengembangan kelembagaan pasca-konflik - Trijono, Lambang (Jurnal Ilmu Sosial dan Ilmu Politik, 2009)
After the peace agreement Indonesia now in the post conflict era and many conflicts in the various part of Indonesia decreased. Democratization and decentralization brings improvement to the social, economic, and security condition in the society. This paper discuss the challenges of the post-conflict in various parts of Indonesia. The main focus of this paper is the approach and the strategy of post-conflict peace building in order to establish peace foundation to achieve peace consolidation and sustainable development